2008
DOI: 10.1111/j.1423-0410.2008.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative autologous blood recovery in prostate cancer surgery: in vivo validation using a tumour marker

Abstract: Even though the risk of disseminating tumour cells in prostate cancer surgery by intraoperative autologous blood recovery is not yet fully established, no tumour-specific gene amplification was found after the association of blood filtration and irradiation, suggesting a significant reduction of such risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…In gynae-oncology, Catling and colleagues [9], who studied the patients undergoing major surgery for endometrial, cervical and ovarian cancer, demonstrated that after passing salvaged blood through LDF, only tumour fragments which were not capable of causing metastasis could be found in the salvaged blood. Similarly, researchers in uro-oncology [21], thoracic-oncology [24] and hepatobiliary oncology [23,25] added the evidence by showing that passage of salvaged blood through IOCS-LDF could lead to no tumour cells in the post-LDF samples. Our findings were consistent with these findings by showing that IOCS-LDF processed blood was devoid of tumour cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In gynae-oncology, Catling and colleagues [9], who studied the patients undergoing major surgery for endometrial, cervical and ovarian cancer, demonstrated that after passing salvaged blood through LDF, only tumour fragments which were not capable of causing metastasis could be found in the salvaged blood. Similarly, researchers in uro-oncology [21], thoracic-oncology [24] and hepatobiliary oncology [23,25] added the evidence by showing that passage of salvaged blood through IOCS-LDF could lead to no tumour cells in the post-LDF samples. Our findings were consistent with these findings by showing that IOCS-LDF processed blood was devoid of tumour cells.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the above fact, evidence has accumulated supporting the use of IOCS in different surgical disciplines, i.e. gynaecological, hepatobiliary, gastrointestinal, urological and lung cancer surgery [12][13][14][15][16][17][18][19][20][21]. Other studies provided evidence that if leucocyte depletion filter (LDF) is added, the combination could eliminate all tumour cells from salvaged blood, rendering it safe [3,9,22,23].…”
Section: Introductionmentioning
confidence: 93%
“…The duration of the procedure is 6-15 minutes and is a complicated logistic process. However, combination of leukocyte filtration with irradiation has been found to remove all active tumour cells (Poli et al 2008). Detailed studies showed that irradiation does not damage the red cells and that recovery in the first the 24 hours is improved, presumed due to selective loss of senescent erythrocytes (Hanssen et al 2002).…”
Section: Tumour Surgerymentioning
confidence: 99%
“…These are ex vivo studies using oncologic cell lines that are seeded in banked or fresh blood 45,[51][52][53][54][55][56] or primary tumour cells collected at the time of tumour resection 48,49,[57][58][59] and then processed via ICS and subsequent LR filtration. Together, these studies show that advanced generation LR filters are very effective in the removal of tumour cells after ICS processing (the results of experiments where tumour cells were NOT completely removed are recorded in bold print in Table 1).…”
Section: Filtrationmentioning
confidence: 99%
“…62 Studies have shown that tumour cells remaining in the red cell concentrate of blood collected and processed with ICS can be effectively eliminated with gamma irradiation (25-50 Gy), as they are rendered mitotically inactive. This was shown both immediately post irradiation 58,62 and following a period of in vitro culture to assess for any occult viable cells 62 (Table 2). However, a subsequent study comparing the efficacy of irradiation with LR filters found irradiation to be less effective.…”
Section: Irradiationmentioning
confidence: 99%